An Analysis of the School Environment on the Character Formation of Fourth Grade Students at SDN 01 Ulak Karang Padang - Nanda Putra Utama; Gusnita Efrina; Gingga Prananda; Yona Syaida Oktira (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Education in Indonesia is expected to produce students with good character. However, initial observations at SDN 01 Ulak Karang Padang found indications of a lack of religious and moral character among some students. This study aims to analyze the influence of the school environment on the character development of fourth-grade children and identify influencing factors. The research method used was a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that the school environment has a positive influence on the development of children's character, particularly in aspects of religiosity, manners, and environmental awareness. However, several obstacles, such as the lack of religious facilities, hinder some students' participation. Factors influencing student character development include family, teachers, the surrounding environment, and learning media. In conclusion, although the school environment plays a positive role, ongoing efforts are needed from all parties, especially teachers as role models, to optimize student character development.